Student voice: perceptions of fair treatment in a Foundations program. (25th January 2019) - Gallagher, Kay
Abstract : Purpose: The purpose of this paper is to investigate why beginning university Emirati students might believe they are unfairly treated by their instructors. By understanding student perceptions, the learning needs of such students can be better catered for, and learning outcomes enhanced. Design/methodology/approach: An interpretivist approach was taken to investigate a finding from a standardized survey of student satisfaction which showed that students felt they were treated unfairly by their instructors. Focus group interviews were used to uncover the possible reasons why students believed they received unfair treatment. Findings: Interpersonal or interactional unfairness is the type of unfair treatment most often cited by the Foundation students who participated in this study, indicative of the importance of interpersonal relations in the United Arab Emirates (UAE) higher education teaching and learning environment. Research limitations/implications: Although the study is situated within one Foundations program in the UAE, the imperative for instructors to build positive interpersonal relationships with beginning students is highlighted, as well as the need for curricular transparency and ongoing moderation of grading practices, and the importance of informing students about these practices. Practical implications: The imperative of building positive pedagogical relationships with beginning university Arab Gulf students is highlighted, as well as the need for transparent practices such as moderation of grades, and explicitly informing students about fair practices. Social implications: Drawing on data from faculty instructors, the paper suggests that a deeper, macrosystemic level of educational unfairness may also be at play: that is, the unfairness inherent in the hegemony of English, and the disconnect between the quality of the state school system and the demands of university. Until these educational issues are addressed, perceptions of unfair treatment in Foundations programs in the Gulf are likely to continue. Originality/value: As higher education continues to undergo expansion and transformation in the UAE, increasing numbers of academic staff from around the world migrate there, and thousands of Gulf students continue to emigrate to study overseas. This paper contributes important insights into Gulf students' perceptions.